Design & Simulation Of 64-Bit Hybrid Processor Instruction Set Using Verilog - M S, Harish M S; D, Jayadevappa (International Journal of Engineering and Technology, 2018)
As a part of my ongoing research on implementation of multi core hybrid processor on FPGA, I have developed data flow designs for most popularly used 20 processor instructions.Â  I have made digital design, wrote code in Verilog HDL and simulated all the 20 instructions using Xilinx ISE 14.5. The data flow designs, symbolic representation and simulation results are explained in detail in this technical paper. This is partial implementation of Hybrid Processor & the other sub modules implementation on Xilinx FPGA will be published in my subsequent technical paper.Â